Directing verbatim theatre as a pleasure activist - Chong, Gua Khee (Taideyliopiston Teatterikorkeakoulu, 2026)
Verbatim theatre is commonly thought of as a form of political theatre that is meaningful but dense. What if we (re)imagine verbatim theatre through the lens of ‘pleasure activism’, a concept coined by writer and activist adrienne maree brown in her book 'Pleasure Activism: The Politics of Feeling Good' (2019)? Where might we as makers and collaborators locate pleasure in this form, and why is this important? This thesis sets out to answer these questions in three parts. In Part I, I review relevant literature on verbatim and documentary theatre and situate my work within this landscape. Next, I set out brown’s concept of ‘pleasure activism’ (2019), and propose short interpretations of her pleasure principles as starting points to work with the concept across the entire arc of verbatim theatre-making. Part III examines the value of autoethnography as a methodology for the purposes of this research and addresses some concerns about its usage. Following this, I apply an autoethnographic lens alongside brown’s pleasure principles to reflect on the process of creating and directing 'From me to you: How shall we eat v1.0' (2026) - a work in which verbatim text, music, and cooking are woven together as a way to invite audiences to consider the impact of their food choices on themselves and the environment. As a conclusion, I offer short reflections on the scope of this thesis, summarise the possibilities of pleasure in verbatim theatre-making and reiterate its importance to the field, as well as share my broader hopes around this work.
Keywords: verbatim-tekniikka; documentary theatre; pleasure activism; autoethnography; Theater--Production and direction.; Verbatim theater.; Pleasure.; teatteritaide; teatteriohjaus; dokumenttiteatteri; poliittinen teatteri; autoetnografia; mielihyvä; aktivismi; fi=ohjaus|sv=regi|en=Directing|